Strengthening the Character of Students' Learning Discipline Through Youtube Media - Nursinta Dewi, Nita; Muhroji (Perspektif Ilmu Pendidikan, 2023)
The focus of this research is to: 1) Understand the teacher's role in character building in Mim Krakitan Bayat. 2) Analyze the methods used by the teacher to strengthen student learning discipline using YouTube media. 3) Identify teachers' challenges and solutions to improving the character of learning discipline. Research approach: descriptive-qualitative. Data: observation, interviews, documentation, analyzed inductively. Result: Teaching the character of discipline through YouTube at Mim Krakitan Bayat brings positive changes to students' behavior. They become more disciplined in terms of collecting assignments, homework, time management while studying, polite behavior in class, and a more regular study pattern. The teacher's role in strengthening the character of learning discipline has proven to be very significant because it forms the mindset and behavior of discipline from an early age. The use of the YouTube platform as a reinforcement tool is also very effective because it is easier for students to understand and apply concepts through the visual format presented in the video. Within a certain period of time, positive changes in students become increasingly visible. In the process of strengthening character, teachers face several challenges, but they manage to overcome them with creativity and the right strategy. These solutions help teachers build and strengthen student discipline in learning contexts.